The regional distribution of unemployment. A microeconomic perspective - Enrique López-Bazo; Elisabet Motellón (European Regional Science Association (ERSA), 2011)
Regional disparities in unemployment rates are large and persistent, particularly in some economies such as Spain. Previous contributions to the literature have provided evidence on their magnitude and evolution, as well as on the role of some economic, demographic and environmental factors in explaining the gap between low and high unemployment regions. Most of these studies have used an aggregate approach. That is, they have not accounted for the individual characteristics of the unemployed and the employed in each region. This paper aim at filling this gap, as it addresses the analysis of regional differentials in unemployment rates by using the information from the Spanish wave of the Labour Force Survey. An appropriate decomposition of the regional gap in the average probability of being unemployed allows us to tell the contribution of differences in the regional distribution of individuals' characteristics from that attributable to a different impact of these characteristics on the probability of unemployment. The results suggest that the well-known disparities in regional unemployment are not just the result of regional heterogeneity in the distribution of individual and job characteristics. Non-negligible differences in the probability of unemployment remain after controlling for that type of heterogeneity, as a result of differences across regions in the effect of the individual characteristics. Among the factors considered in the analysis, regional differences in the individuals' endowment of human capital, and in its effect, play an outstanding role.
Keywords: 330